2019
DOI: 10.1542/peds.2018-1511
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots for Hospitalized Children

Abstract: BACKGROUND AND OBJECTIVES: Social robots (SRs) are increasingly present in medical and educational contexts, but their use in inpatient pediatric settings has not been demonstrated in studies. In this study, we aimed to (1) describe the introduction of SR technology into the pediatric inpatient setting through an innovative partnership among a pediatric teaching hospital, robotics development, and computational behavioral science laboratories and (2) present feasibility and acceptability data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 34 publications
(26 reference statements)
2
61
0
2
Order By: Relevance
“…Social robots have been highly effective for increasing social interactions and communication for children with autism (Fernaeus et al, 2010;Scassellati et al, 2012;Kim et al, 2013). In addition, social robots have been shown to reduce anxiety in children who are hospitalized (Jeong, 2017;Logan et al, 2019). Little work has specifically explored the relationship between teens and social robots.…”
Section: Assistive Social Robotsmentioning
confidence: 99%
“…Social robots have been highly effective for increasing social interactions and communication for children with autism (Fernaeus et al, 2010;Scassellati et al, 2012;Kim et al, 2013). In addition, social robots have been shown to reduce anxiety in children who are hospitalized (Jeong, 2017;Logan et al, 2019). Little work has specifically explored the relationship between teens and social robots.…”
Section: Assistive Social Robotsmentioning
confidence: 99%
“…Robotic devices are a promising intervention as they provide elements of distraction to children undergoing stressful and painful medical experiences . A recent study demonstrated that a robotic bear improved hospitalized children's mood more than a stuffed animal or application version of the bear . Animatronic devices have also been shown to reduce physiologic distress among children aged 2‐7 years undergoing radiation therapy procedures and to improve coping .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A recent study demonstrated that a robotic bear improved hospitalized children's mood more than a stuffed animal or application version of the bear. 11 Animatronic devices have also been shown to reduce physiologic distress among children aged 2-7 years undergoing radiation therapy procedures 12 and to improve coping. 13 Beran et al found that children interacting with a robotic device during vaccination had reduced experiences of pain.…”
Section: Introductionmentioning
confidence: 99%
“…No que se refere às necessidades emocionais de pacientes pediátricos e suas famílias no contexto hospitalar, Logan et al (2019) realizaram um estudo empregando robôs sociais com 54 crianças de 3 a 10 anos de idade. Tais robôs eram, basicamente, ursinhos de pelúcia interativos.…”
Section: Introductionunclassified